Hubungan Prokrastinasi Akademik dengan Ketidakjujuran Akademik pada Mahasiswa Kedokteran - Paskila, Carissa N.; Berhimpon, Siemona L. E.; Tewal, Florensia B. (Medical Scope Journal, 2025)
Abstract: Academic procrastination is commonly exhibited among students, which often leads to academic dishonesty. This issue is a significant concern in the educational world, where academic dishonesty contradicts the goals of education as a means of developing personal potential and building individual character. This study aimed to evaluate the relationship between academic procrastination and academic dishonesty among students of year 2021 of Faculty of Medicine Universitas Sam Ratulangi. This was an observational and analytical study with a cross-sectional design. Primary data collection utilized the Procrastination Assessment Scale-Students and the Academic Practices Survey. There were 186 students as respondents. The majority of respondents exhibited moderate level of academic procrastination (95.2%) and moderate levels of academic dishonesty (57.5%). The Spearman test for the relationship between academic procrastination and academic dishonesty yielded a correlation coefficient of 0.328 and a significance value of p<0.001. In conclusion, there is a positive relationship between academic procrastination and academic dishonesty among the medical students of year 2021 at Faculty of Medicine, Universitas Sam Ratulangi. Keywords: academic procrastination; academic dishonesty; medical education Abstrak: Prokrastinasi akademik merupakan perilaku yang sering dilakukan di kalangan mahasiswa yang sering kali berujung pada perilaku ketidakjujuran akademik. Hal ini menjadi perhatian penting dalam dunia pendidikan, di mana perilaku ketidakjujuran akademik tidak sesuai dengan tujuan pendidikan sebagai wadah pengembangan potensi diri dan membangun karakter individu. Penelitian ini bertujuan untuk mengetahui hubungan antara prokrastinasi akademik dengan ketidakjujuran akademik pada mahasiswa Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi (PSPD FK Unsrat). Jenis penelitian ialah observasional analitik dengan desain potong lintang. Pengambilan data primer menggunakan kuisioner Procrastination Assessement Scale-Students dan Academic Practices Survey. Responden penelitian ialah angkatan 2021 PSPD FK Unsrat. Hasil penelitian mendapatkan 186 mahasiswa sebagai responden penelitian. Sebagian besar responden memiliki tingkat perilaku prokrastinasi akademik sedang (95,2%) dan tingkat ketidakjujuran akademik sedang (57,5%). Hasil uji Spearman terhadap hubungan antara prokrastinasi akademik dengan ketidakjujuran akademik mendapatkan nilai koefisien korelasi sebesar 0,328 dan nilai signifikansi p<0,001. Simpulan penelitian ini ialah terdapat hubungan positif yang bermakna antara prokrastinasi akademik dengan ketidakjujuran akademik pada mahasiswa angkatan 2021 Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi. Kata kunci: prokrastinasi akademik; ketidakjujuran akademik; pendidikan kedokteran